Research on Strategies for the Construction of Community Education Quality Evaluation System in China (Journal of Global Humanities and Social Sciences, 2024)
Community education aims to improve the quality of life of citizens in a country. It is considered to be an important part of lifelong education. In China, community education has been seen as a key means of enhancing national quality and fostering social harmony to meet the increasing demands of the economy and society’s rapid development. The paper first sets the scenario addressing the definition of community education quality and its connotation and then explores the strategies for quality and systemic evaluation of community education in practice. Lastly, the paper analyses the challenges and opportunities for community education by proposing the prospective future of community education evaluation.